A framework for long‐term scenario analysis in the Taihu Basin, China. Issue 1 (5th February 2013) - Cheng, X.T.; Evans, E.P.; Wu, H.Y.; Thorne, C.R.; Han, S.; Simm, J.D.; Hall, J.W.
Abstract: The Taihu Basin, situated on the south side of the Yangtze delta, is a large flood‐prone area that has urbanised rapidly. The risk of flooding is set to increase in future because of continued economic development and the impacts of climate change. Scenario analysis has been adopted to help understand the potential impacts of long‐term change on flood risk, including the effects of climate change and socio‐economic development, thus providing the basis for the development of sustainable flood risk management strategies. This paper describes the flooding processes in the Taihu Basin and sets out strategic questions that the scenario analysis sought to address. It provides an overview of the assessment framework adopted in the China/UK scientific cooperation project 'China–UK Scenario Analysis Technology for River Basin Flood Risk Management in the Taihu Basin'. Further details of the component studies carried out as part of the project are given in the associated papers in this special issue.